PENINGKATAN HASIL BELAJAR IPA SISWA KELAS V SDN 122 MANGOTTONG KECAMATAN SINJAI UTARA KABUPATEN SINJAI MELALUI METODE PERMAINAN MENCARI JEJAK - Sudarto Sudarto; Mujahidah Mujahidah; Miftah Farid (Bajang Institute, 2024)
This research is a Classroom Action Research (car) with the aim of improving THE science learning outcomes by applying the game method of finding traces of the Fifth Grade students at SDN 122 Mangottong with in totally of 18 students. The collection techniques data in this study were tests and observations. Data analysis techniques used data collection, data reduction, presentation and conclusion drawn. The results showed that the percentage of the teacher activity in the first cycle of meeting 1 was of 62.95% (Adequate) and in meeting 2 reached of 66.65% (Adequate), while in the second cycle of meeting 1 it was of 81.47% (Good) and in meeting 2 it reached of 88.88% (Good). The percentage of student activity in the first cycle of meeting 1 was of 51.84% (Less) and meeting 2 reached of 62.95% (Adequate). Meanwhile, the percentage in the second cycle of meeting 1 was of 77.77% (Good) and meeting 2 reached of 81.47% (Good). In the first cycle, there were 10 out of 18 students who completed with an average score of 70 with a percentage of learning completion reaching of 55.55% (Adequate), while in the second cycle there were of 14 out of 18 students who achieved a complete score with an average score of 81 with a percentage of learning completion reaching of 77.77% (Good). It can be concluded that the Trace Finding Game Method can improve student learning outcomes.